2020
DOI: 10.1029/2018jc014860
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Features of Barotropic and Baroclinic Tides in the Northwestern South China Sea

Abstract: Seven seasonal moorings distributed over the shelf and slope east of Hainan Island and south of western Guangdong Province are used to investigate the seasonal characteristics of barotropic and baroclinic tides in the northwestern South China Sea (NWSCS). The barotropic K 1 current intensified during summer over the shelf sites. The diurnal baroclinic tides are much more prominent than the semidiurnal tides at each mooring site. Over the continental shelf, accompanied by large phase speeds and wavelengths, bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 71 publications
(133 reference statements)
2
12
0
Order By: Relevance
“…The velocity vectors rotate clockwise at H03 and H04 and rotate anticlockwise at H05 and the MR site. The direction of the major axis of the K 1 tide is consistent with the result in Yan et al (2020), while the rotation is opposite. With regard to the M 2 constituent, the direction of the major axis changes from NW-SE off shore (at H04-05) to NE-SW onshore (at H03) in the north; it is the same direction as the K 1 tide at the MR site.…”
Section: Barotropic Tidesupporting
confidence: 84%
See 3 more Smart Citations
“…The velocity vectors rotate clockwise at H03 and H04 and rotate anticlockwise at H05 and the MR site. The direction of the major axis of the K 1 tide is consistent with the result in Yan et al (2020), while the rotation is opposite. With regard to the M 2 constituent, the direction of the major axis changes from NW-SE off shore (at H04-05) to NE-SW onshore (at H03) in the north; it is the same direction as the K 1 tide at the MR site.…”
Section: Barotropic Tidesupporting
confidence: 84%
“…There are previous studies showing the long-range westward propagation of the internal K 1 and M 2 tide generated at the Luzon Strait based on satellite observations (Zhao, 2014) and numerical modeling (Xu et al, 2016;Yan et al, 2020), which can propagate across the deep basin and arrive at the western continental slope (though it decreases when propagating to the west and is rather small relative to that in the far east), suggesting that the energy fl ux of internal tide near the successive stations probably indicates the feature of the internal tide propagated far away from the east. Moreover, Xu et al (2016) showed remarkable barotropic to baroclinic conversion rate of K 1 tide along the northern continental slope of South China Sea, and Yan et al (2020) revealed that the slope region around 200-m depth in the southeast of Hainan Island is generation region of baroclinic M 2 tide and the barotropic to baroclinic conversion rate along the slope is signifi cant in winter, suggesting the possible eff ect from the generated internal tide along the slope on the energy fl ux and the westward propagation to the study area. However, this issue needs support of more data and is out of this paper's scope and will be investigated in the future.…”
Section: Propagation Of the Internal Tidementioning
confidence: 99%
See 2 more Smart Citations
“…Li et al (2008) and Z. Xu et al (2010), Su and Pohlmann (2009), Liang et al (2019), D. Li et al (2011 and Yan et al (2020), and J. Xu, Chen, et al (2016), respectively.…”
Section: Nliw Occurrence Frequencymentioning
confidence: 99%